Diels-Alder reactions of food relevant compounds under high pressure: 2,3-dimethoxy-5-methyl-p-benzoquinone and myrcene - Kübel, Jörg-Andreas; Ludwig, Horst; Tauscher, Bernhard (High pressure food science, bioscience and chemistry, 1998)
Foods pasteurized by hydrostatic high pressure have already been marketed in Japan. There is great interest in this method also in Europe and USA. Tem…